The Effectiveness of Guidance Programs for Inmates in the Process of Social Reintegration (A Study at Wonogiri Class IIB Prison) - Ali Dzaini Wardi; Briliyan Ernawati; Hasna Afifah (Green Publisher Indonesia, 2026)
The passage of Law Number 22 of 2022 marks a fundamental shift in Indonesia's correctional system from a retributive approach to one oriented toward social reintegration. This study aims to analyze the effectiveness of the guidance program at the Class IIB Wonogiri Correctional Institution, identify supporting and inhibiting factors, and evaluate the reintegration readiness of the Assisted Residents. Using an empirical juridical method with a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis. The results of the study show partial effectiveness: personality development programs have succeeded in restoring mental stability, while independence programs have not been substantially effective due to infrastructural stagnation and curriculum incompatibility. The analysis reveals the existence of a dialectic in which the humanistic dedication of officers as a supporting factor is overshadowed by dominant inhibiting factors, namely limited facilities and persistent social stigma. This condition creates the phenomenon of “Paradoxical Reintegration,” in which the Fostered Citizens possess psychological readiness (internal desistance) but face structural rejection from society and the labor market. This study concludes that without structural interventions, such as social enterprises or affirmative policies, the legal mandate of reintegration cannot be fully realized.